Restrukturisasi Kredit Bermasalah selama Pandemi Covid-19 di Bank Mandiri Mikro Pontianak - Marsela Diaz; Syarifah Novieyana; Anistya Fitri Larasati (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
Bank is a financial institution whose main form of activity is to make loan to the public. However, the implementation of credit distribution does not always run smoothly as bank are usually faced with the risk of non-performing loans. Therefore, Bank Mandiri Mikro Pontianak rescued non-performing loans by improving credit quality through credit restructuring. The credit restructuring carried out is an effort to realize the stability of the banking financial system as regulated in government regulations in the provisions of the Otoritas Jasa Keuangan Regulation Number 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the 2019 Coronavirus Disease Spread. The purpose of this study is to find out the factors that lead to non-performing loans and how to resolve these non-performing loans during the COVID-19 pandemic at Bank Mandiri Mikro Pontianak. Data collection techniques used are interviews and documentation studies. The data analysis technique is qualitative with data collection, data reduction, data presentation and conclusions. The research findings have revealed that non-performing loans during the covid-19 pandemic were caused by external bank factors originating from unintentional elements by the debtor, and the settlement of non-performing loans with credit restructuring was carried out by extending the term and reducing interest arrears. The outputs produced in this research are scientific publications in national journals.